Bisociative Knowledge Discovery : An Introduction to Concept, Algorithms, Tools, and Applications. - Berthold, Michael R. (Berlin, Heidelberg : Springer Berlin / Heidelberg, 2012)
The focus of this book, and the BISON project from which the contributions originate, is a network based integration of data repositories of a variety of types, and the development of new ways to analyse and explore the resulting gigantic information networks.
The Future of Bisociative Reasoning and Cross-Context Data Mining.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books